2022
DOI: 10.3390/molecules27175620
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Potential of Pre and Pro-Vitamin D of Mushrooms against Mpro and PLpro Proteases of COVID-19: An In Silico Approach

Abstract: Vitamin D’s role in combating the SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), the virus causing COVID-19, has been established in unveiling viable inhibitors of COVID-19. The current study investigated the role of pre and pro-vitamin D bioactives from edible mushrooms against Mpro and PLpro proteases of SARS-CoV-2 by computational experiments. The bioactives of mushrooms, specifically ergosterol (provitamin D2), 7-dehydrocholesterol (provitamin-D3), 22,23-dihydroergocalciferol (provitamin-D4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…The findings also point to the potential for expediting the structure-based identification and optimization of a new COVID-19 therapeutic candidate by using simulation-refined models of protein-ligand complexes. Few similar works have been reported so far on 25-hydroxy vitamin D against the main protease (M pro ) and RNA-dependent RNA polymerase (RdRP) [ 81 ], Mpro and PLpro [ 82 , 83 ], endoribonuclease Nsp15 [ 84 ], etc. with impressive docking scores of >−10 Kcal/mol.…”
Section: Discussionmentioning
confidence: 99%
“…The findings also point to the potential for expediting the structure-based identification and optimization of a new COVID-19 therapeutic candidate by using simulation-refined models of protein-ligand complexes. Few similar works have been reported so far on 25-hydroxy vitamin D against the main protease (M pro ) and RNA-dependent RNA polymerase (RdRP) [ 81 ], Mpro and PLpro [ 82 , 83 ], endoribonuclease Nsp15 [ 84 ], etc. with impressive docking scores of >−10 Kcal/mol.…”
Section: Discussionmentioning
confidence: 99%
“…The time-dependent uctuation of Rg (radius of gyration) was estimated to establish the in uence of ligand binding on the compactness and structural integrity of ligand-A3P and TaSOT proteins. TaSOT5b-2D shows higher Rg, than other two proteins, that indicates that the higher the Rg higher will be the level of labile nature of the complexes, whereas the lower Rg pro le indicates the contracted nature of the complexes (Tiwari et al 2022).…”
Section: )mentioning
confidence: 90%
“…For example, many studies have reported that GRL-0617 inhibits viral replication of SARS-CoV-2 because its binding site and mode of inhibition are almost identical to that of SARS-CoV PL pro , and these results further consolidate the position of PLpro as a drug target for antiviral therapy of COVID-19 [ 11 , 12 , [117] , [118] , [119] , [120] ]. Therefore, it is an attractive target for antiviral drug development [ 12 , [121] , [122] , [123] ]. For example, Zhao et al, designed an approach using a SARS-CoV-2 PL pro inhibition activity as the primary screening tool for the discovery of the small molecule inhibitors, with a secondary cell-based assay for evaluation of their antiviral activity.…”
Section: Treatments For Covid-19mentioning
confidence: 99%